Associations of protein intake in early childhood with body composition, height, and insulin-like growth factor I in mid-childhood and early adolescence. Issue 4 (14th March 2019) - Switkowski, Karen M; Jacques, Paul F; Must, Aviva; Fleisch, Abby; Oken, Emily
ABSTRACT: Background: Early protein intake may program later body composition and height growth, perhaps mediated by insulin-like growth factor I (IGF-I). In infancy, higher protein intake is consistently associated with higher IGF-I concentrations and more rapid growth, but associations of protein intake after infancy with later growth and IGF-I are less clear. Objectives: Our objective was to examine associations of protein intake in early childhood (median 3.2 y) with height, IGF-I, and measures of adiposity and lean mass in mid-childhood (median 7.7 y) and early adolescence (median 13.0 y), and with changes in these outcomes over time. We hypothesized that early childhood protein intake programs later growth. Methods: We studied 1165 children in the Boston-area Project Viva cohort. Mothers reported children's diet using food-frequency questionnaires. We stratified by child sex and examined associations of early childhood protein intake with mid-childhood and early adolescent BMI z score, skinfold thicknesses, dual-energy X-ray absorptiometry (DXA) fat mass, DXA lean mass, height z score, and IGF-I concentration. We adjusted linear regression models for race/ethnicity, family sociodemographics, parental and birth anthropometrics, breastfeeding status, physical activity, and fast food intake. Results: Mean protein intake in early childhood was 58.3 g/d. There were no associations of protein intake in early childhood with any of the mid-childhood outcomes. Among boys, however, each 10-g increase in early childhood total protein intake was associated with several markers of early adolescent size, namely BMI z score (0.12 higher; 95% CI: 0.01, 0.23), DXA lean mass index (1.34% higher; 95% CI: −0.07%, 2.78%), and circulating IGF-I (5.67% higher; 95% CI: 0.30%, 11.3%). There were no associations with fat mass and no associations with any adolescent outcomes among girls. Conclusions: Early childhood protein intake may contribute to programming lean mass and IGF-I around the time of puberty in boys, but not to adiposity development. This study was registered at clinicaltrials.gov as NCT02820402.